Konovalov's first law validity in binary twophase systems. - T. V. Chelyuskina; A. V. Frolkova; Ye. A. Sharonova (Тонкие химические технологии)
Complete conditions for the validity of Konovalov's first law in binary ideal and not ideal two-phase systems are found.